Duration and clinical outcomes of dual antiplatelet therapy following percutaneous coronary intervention for acute coronary syndrome: A multicentre “real-world practice” registry-based study - Vergara-Uzcategui, Carlos E.; Moreno, Víctor H.; Hennessey, Breda; Sánchez-del-Hoyo, Rafael; Donis, José H.; Gonzalez-Rojas, Jorgelys; Salinas, Pablo; Nombela-Franco, Luis; Gonzalo, Nieves; Jimenez-Quevedo, Pilar; Mejia-Renteria, Hernán; Escaned, Javier; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background The optimal duration of dual antiplatelet therapy (DAPT) ought to be determined taking into account individual ischaemic or bleeding events risks. To date, studies have provided inconclusive evidence on the effects of prolonged DAPT. We sought to evaluate the long-term outcomes of this strategy following percutaneous revascularization in the context of acute coronary syndrome (ACS). Methods Retrospectively from four centers in Madrid, we identified 750 consecutive ACS patients, divided in two groups of DAPT duration: <13 months and >13 months, with a mean follow-up of 48 months. Results Patients with DAPT > 13 months had a higher non-adjusted incidence of Major Adverse Cardiovascular Events (11.6% vs. 17.3%) and new revascularization (3.7% vs. 8.7%). Differences in all-cause death, cardiac death, myocardial infarction, stent thrombosis and stroke were non-significant. There was no difference in the incidence of major bleeding (7.4% vs. 6.3%). Multivariable Cox regression analysis showed that the independent risk predictors of MACE were age (HR: 1.04, 95% CI: 1.02–1.06, p < 0.001) and multivessel disease (HR: 2.29, 95% CI: 1.32–3.95, p = 0.003), whereas the independent protective predictor was normal hemoglobin (HR: 0.88, 95% CI: 0.78–0.98, p = 0.022). Conclusions In this real-world registry cohort of ACS patients treated with PCI and 1 year of DAPT in Spain, we report a trend of increased rate of MACE and new revascularization not associated with TVR in patients with longer DAPT. Our findings support the need for future randomized controlled trials to confirm or refute these results.